PENDIDIKAN ISLAM DALAM KONSEPSI LEMBAGA DAN AJARAN - Moh Asvin Abdurrohman (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2022)
Islamic boarding school education today can be classified into three forms. First, Islamic boarding schools, whose education and teaching methods use the sorogan or dam method, namely a kyai, teach students based on classical books written in Arabic by medieval scholars with a translation system. Generally, this kind of Islamic Boarding School is "sterile" from general knowledge. People usually call it by the name of the Salaf Islamic Boarding School. Second, Islamic boarding schools, in addition to maintaining the education and teaching system mentioned above, also include general education. Third, Islamic boarding schools in their education and teaching system integrate the madrasa system into pesantren with all their souls, values ​​and other attributes, and their teaching uses the classical system plus with strict discipline with full dormitories or students are required to stay in the dormitory.The specific purpose of pesantren education in question is to prepare students to become pious people in the religious knowledge taught by the kyai concerned and to practice it in society. Meanwhile, the general purpose of pesantren is to guide students to become human beings with Islamic personalities who are able with their religious knowledge to become Islamic missionaries in the surrounding community through their knowledge and deeds.